THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL ON STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITY - Dewi Purnama Sari; Azizah Yusra Amaliyah; Lilis Arini (Universitas Labuhanbatu, 2023)
The issue in the exploration is the low capacity of class understudies to tackle numerical questions. XI SMAS PAB 5 Klumpang. This review plans to decide if there is an impact of the Logical Instructing And Learning (CTL) learning model on the numerical critical thinking skills of Class XI SMAS PAB 5 Klumpang. This sort of examination is trial research with a One Gathering Pretest-Posstest Plan. The populace in this review were all understudies of class XI SMAS PAB 5 Klumpang, while the example in this review was class XI-B, which comprised of 30 understudies. The information in this review were dissected utilizing a basic straight relapse test. The typical trial of numerical critical thinking abilities when acquiring is 56.86 and 67.53. To figure out how much impact the Relevant Educating And Learning (CTL) learning model has on numerical critical thinking skills a straightforward direct relapse test is utilized with the consequence of rcount which is 6.81 which is more noteworthy than the worth of rtable with a huge degree of 5% (0.05) and df 30 to be specific 1.70 (6.81 > 1.70) so H0 is dismissed and Ha is acknowledged, intending that at a critical degree of 62.41% there is a critical impact between the Context oriented Instructing And Learning (CTL) learning model and understudies' numerical critical abilities to think. Hence one might say that the Context oriented Educating And Learning (CTL) learning model impacts understudies' numerical critical thinking skills .Keywords: Contextual Teaching And Learning (CTL) Learning Model , Mathematical Problem Solving AbilityÂ AbstrakMasalah dalam penelitian adalah rendahnya kemampuan pemecahan masalah matematika siswa kelas. XI SMAS PAB 5 Klumpang. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh model pembelajaran Contextual Teaching And Learning (CTL) terhadap kemampuan pemecahan masalah matematika siswa Kelas XI SMAS PAB 5 Klumpang. Jenis penelitian ini adalah penelitian eksperimen dengan design penelitian One Group Pretest-Posstest Design. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMAS PAB 5 Klumpang, sedangkan sampel dalam penelitian ini yaitu kelas XI-B yang berjumlah 30 siswa. Data dalam penelitian ini dianalisis menggunakan uji regresi linier sederhana. Rata-rata tes kemampuan pemecahan masalah matematika sebelum dan sesudah pembelajaran adalah 56,86 dan 67,53. Untuk mengetahui seberapa besar pengaruh model pembelajaran Contextual Teaching And Learning (CTL) terhadap kemampuan pemecahan masalah matematika digunakan uji regresi linier sederhana dengan hasil rhitung yaitu 6,81 yang lebih besar dari nilai rtabel dengan taraf signifikan 5% (0,05) dan df 30 yaitu 1,70 (6,81 > 1,70) sehingga H0 ditolak dan Ha diterima, artinya pada taraf signifikan 62,41% terdapat pengaruh yang signifikan antara model pembelajaran Contextual Teaching And Learning (CTL) dan kemampuan pemecahan masalah matematika siswa. Dengan demikian dapat dikatakan bahwa model pembelajaran Contextual Teaching And Learning (CTL) berpengaruh terhadap kemampuan pemecahan masalah matematika siswa.Kata Kunci: Model Pembelajaran Contextual Teaching And Learning (CTL), Kemampuan Pemecahan Masalah Matematika